Systematic Literature Review (SLR) : Analisis Implementasi Pajak Pertambahan Nilai (PPN) E-Commerce dan Pajak atas Penjualan Barang Mewah (PPNBM) pada Sekyor Industri Otomotif di Indonesia - Situngkir, Tiar Lina; Ramadhan, Muhammad Rizki; Ramadhan, Mulky Ismail; Husnina, Najla Nurul ,; Azzahra, Raisya Putri Syafna; Wijaya, Sandika Naufal Fawaz; Sinta Aji, Sekar Nirwana Ros; Lestari, Sri Ayu; Sasmita, Tegar Permata; Marsyantrinisa, Yossy; Novelina, Riani Rahma (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The government faces difficulties in handling tax matters, especially income tax from online sales, because the rapid progress of the business world is not always matched by advances in the legal system. It remains difficult to determine the amount of tax owed and monitor e-commerce activities. Meanwhile, the majority of the APBN is financed by taxes. Income Tax (PPh) provides the largest income for the country, followed by Value Added Tax (PPn) and Sales Tax on Luxury Goods (PPnBM). The research method used is the Systematic Literature Summary (SLR) Method where only 20 publications on the Analysis of the Application of Value Added Tax (VAT) in the E-commerce Sector and Sales Tax on Luxury Goods (PPnBM) in the Indonesian Automotive Industry Sector were used in this research. The results of this research show that VAT collection on e-commerce transactions and intensive PPnBM in the Indonesian automotive sector has various impacts on the economy, especially in the long term. However, periodic evaluation is needed to ensure its long-term effectiveness. In addition, tax compliance from medium-sized businesses needs to be improved through a holistic approach involving awareness, knowledge and adequate infrastructure Keywords: Implementation of VAT, Literature Study, PPNBM, VAT in the E-commerce Sector